Training and Development of Community Competence in Managing Tourism - Islahuddin, Islahuddin; Said, Farid; Machmuri, Andri (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Kambo Village, located in Palopo, South Sulawesi, has excellent potential to develop into a tourist destination emphasizing local customs and traditions. However, this potential has not been fully utilized because the quality of tour packages sold to tourists still needs to be improved. This article highlights the importance of developing tour packages in Kambo Tourism Village through a structured approach, which includes initial studies, tour package development, community education, and marketing and sales. This development should be based on a SWOT analysis to identify strengths, weaknesses, opportunities, and threats. Strategies being considered include expanding natural and cultural tour packages, working with travel agencies, digital promotion, and improving facilities and amenities. With the right approach, Kambo Tourism Village can become a competitive and growing tourism destination, making a significant contribution to the economic improvement and welfare of the local community.